Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.envint.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal manganese teeth levels and neurodevelopment at 7, 9, and 10.5years in the CHAMACOS cohort

Abstract: Background Numerous cross-sectional studies of school-age children have observed that exposure to manganese (Mn) adversely affects neurodevelopment. However, few prospective studies have looked at the effects of both prenatal and postnatal Mn exposure on child neurodevelopment. Methods We measured Mn levels in prenatal and early postnatal dentine of shed teeth and examined their association with behavior, cognition, memory, and motor functioning in 248 children aged 7, 9, and/or 10.5 years living near agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 63 publications
8
88
4
Order By: Relevance
“…Generally women in menstruating ages are known to absorb more Mn concentrations than men due to lower iron stores (Finley et al, 1994), which allows increased uptake of Mn via shared transporters such as DMT1 (Au et al, 2008). However, several other studies have shown differences between sexes in Mn related neurotoxic also in early life (Gunier et al, 2015; Mora et al, 2015; Riojas-Rodriguez et al, 2010). Using the same tooth matrix Mn biomarker as the current study, Mora et al and Gunier et al showed that girls were generally more sensitive to early life Mn exposure than boys.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Generally women in menstruating ages are known to absorb more Mn concentrations than men due to lower iron stores (Finley et al, 1994), which allows increased uptake of Mn via shared transporters such as DMT1 (Au et al, 2008). However, several other studies have shown differences between sexes in Mn related neurotoxic also in early life (Gunier et al, 2015; Mora et al, 2015; Riojas-Rodriguez et al, 2010). Using the same tooth matrix Mn biomarker as the current study, Mora et al and Gunier et al showed that girls were generally more sensitive to early life Mn exposure than boys.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have also shown sex differences in the health effects of Mn exposure (Gunier et al, 2015; Menezes-Filho et al, 2011; Riojas-Rodriguez et al, 2010), suggesting that there may be important differences in Mn homeostasis and toxicity between girls and boys. Furthermore, studies in animals and humans have indicated differences in the effects of exposure related to the developmental stage at which the exposure was experienced (Betharia and Maher, 2012; Gunier et al, 2015; Mora et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The use of tooth biomarkers in this PHIME study and the CHAMACOS study conducted by Mora et al (Mora et al, 2015) and Gunier et al (Gunier et al, 2015) has enabled the estimation of effects in different exposure windows in prenatal and early childhood periods, in order to ascertain a more complete perspective of the impact of Mn during early life. It has been suggested that Mn levels in pregnant women are significantly higher than that in non-pregnant women, likely due to the essentiality of Mn for neurodevelopment (Oulhote et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Mora et al (2015) measured Mn levels in prenatal and early postnatal dentine of shed teeth in children living near agricultural fields treated with Mn-containing fungicides in the Center for the Health Assessment of Mother and Children of Salinas (CHAMACOS) cohort in California and found that higher concentrations of prenatal Mn was associated with improved motor outcomes assessed by Finger tapping test at age 7 years and Luria-Nebraska Motor Scale at age 9 and 10.5 years, but only in boys (Mora et al, 2015). They also found sex differences in the associations between early postnatal Mn and these motor function tests, where in general beneficial associations were found in boys but adverse associations were found in girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation